Optimization of Physalis angulata L. callus induction and salinity-induced antioxidant production - Sistyananda, Firstian Naufal; Suminar, Erni; Nuraini, Anne; Kadapi, Muhamad; Murgayanti, Murgayanti; Mubarok, Syariful; Budiarto, Rahmat; Renaldi, Eddy; Kusumiyati, Kusumiyati (Universitas Padjadjaran, 2026)
Groundcherry (Physalis angulata L.) is a plant with many medicinal potentials due to its rich secondary metabolites such as phenolic and flavonoid. However, conventional agriculture practices are still limited, especially in Indonesia. This study was divided into two stages. The first stage was conducted to determine optimal 6-BAP and 2,4-D combination for callus induction, while the second stage was conducted to determine callus phenolic, flavonoid, and antioxidant response to salinity stress. The first stage was arranged in factorial completely randomized design with two factors: 6-BAP (0, 2, and 4 mg/L) and 2,4-D (0, 0.5, 1, and 1.5 mg/L). The second stage was arranged in simple completely randomized design with different NaCl concentration (0, 25, 50, 75, 100 mM) as treatments. The results showed significant interaction (p < 0.05) between 6-BAP and 2,4-D on callus induction. Combination of 2 mg/L 6-BAP and 1 mg/L 2,4-D showed the highest callus formation percentage (46% increase), callus size (60.12% increase), and fresh weight (179.69% increase), and greener compact callus. Application of NaCl as salinity stress at second stage experiment served as an elicitor to enhance callus antioxidant capacity. Salinity level at 100 mM NaCl showed the most accumulation of phenolic content (17.8% increase), flavonoid content (25.17% increase), and antioxidant activities (6.84% IC50 decrease). This study demonstrates plant growth regulator optimization with salinity stress elicitation integration as an effective strategy to enhance antioxidant production in P. angulata callus, providing a practical approach for controlled secondary metabolite production.